Analysis of the application of the project-based learning model to student learning outcomes in chemistry learning with a literature review method - Suci Arta, Herdina; Nabila Putri, Lulu; Puspita, Dona; Rahmawan, Setia (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This study uses a literature review to examine the effectiveness of the Project-Based Learning (PjBL) model in enhancing students' academic performance in chemistry education. Chemistry education frequently faces challenges due to its abstract content and disconnection from students' everyday experiences, which affect their comprehension and result in learning scores that remain below the KKM. The PjBL framework, as a learning innovation, provides a blend of theory and practice that enhances conceptual understanding, boosts critical thinking, fosters creativity, and increases student motivation. The research approach employs a systematic literature review by examining 25 pertinent articles that address the implementation of PjBL in chemistry education. The research findings indicate that the PjBL model effectively enhances student learning outcomes, critical thinking, creativity, and the connection between chemistry content and everyday life. PjBL enhances students' enthusiasm for learning and collaboration, offering a more engaging and significant educational experience. The Project-Based Learning model holds significant promise for enhancing the quality of chemistry education in schools.